Nutritional composition and label evaluation of some commercial dry dog foods in Ibadan, Nigeria (2011)
The nutrient and energy content of commercial dry dog feeds most commonly patronized in the city of Ibadan were analyzed. Most of the feeds carry no specific values of nutrient composition on their labels. The results of proximate analysis of the feeds were compared with mean values of nutrients in the National brand of dry dog food of the USA. Although, the dog feeds were found to be adequate in protein and energy content, they, however, showed appreciably lower values for fat and fiber contents, as well as the levels of most of the micronutrients (Fe, Mn, Zn and Se). Extensive variations were observed in the concentrations of several nutrients among the dog food brands analyzed. While tighter regulations are being advocated for the pet food industry, it will be necessary to perform digestibility and growth studies of these foods in order to establish baseline data on nutritional composition of dog foods marketed in the country.